2019
DOI: 10.1021/acs.jpcc.9b01733
|View full text |Cite
|
Sign up to set email alerts
|

Combined Nuclear Magnetic Resonance and Molecular Dynamics Study of Methane Adsorption in M2(dobdc) Metal–Organic Frameworks

Abstract: We examine the diffusion of methane in the metal-organic frameworks M 2 (dobdc) (M = Mg, Ni, Zn; dobdc 4− = 2,5-dioxido-1,4-benzenedicarboxylate) as a function of methane loading through a combination of nuclear magnetic resonance (NMR) and 1 molecular dynamics simulations. At low gas densities, our results suggest that favorable CH 4 -CH 4 interactions lower the free energy barrier for methane hopping between coordinatively unsaturated metal sites and thus enhance the translational motion of methane down the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…It was found that the self‐diffusion coefficient of methane in M 2 (dobdc) was inversely related to the binding energy at the unsaturated metal sites. [ 80 ]…”
Section: Ssnmr Characterization Of Mofsmentioning
confidence: 99%
“…It was found that the self‐diffusion coefficient of methane in M 2 (dobdc) was inversely related to the binding energy at the unsaturated metal sites. [ 80 ]…”
Section: Ssnmr Characterization Of Mofsmentioning
confidence: 99%
“…We studied the diffusion properties for selected MOFs and zeolites at low loading, and, furthermore, we also applied a new approach to investigate the diffusion in the limit of zero For this case study, we used the same structures and the same LAMMPS files, adopting the same simulation conditions as Witherspoon et al, 14 and repeated the simulations of the diffusion of CH 4 molecules at low loading inside three M 2 (dobdc) structures (M: Mg, Ni, and Zn) at 313 K.…”
Section: Resultsmentioning
confidence: 99%
“…To approach the zero loading limit, one typically tries to reduce the number of molecules and/or increase the size of the simulation cell. This work was triggered by some recent work of Witherspoon et al, 14 who have used a combination of NMR and MD simulations to study the CH 4 diffusion and their binding at the coordinatively unsaturated metal sites in M 2 (dobdc) (M = Mg, Ni, and Zn) frameworks at low and high guests' loading. At low loading, Witherspoon et al observed in the molecular dynamics simulation that the self-diffusion coefficient slowly increases until it reaches a maximum.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of software package for MD simulation, including Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) [35], Chemistry at Harvard Macromolecular Mechanics (CHARMM) [36], Groningen Machine for Chemical Simulations (GROMACS) [37], Nanoscale Molecular Dynamics (NAMD) [38], Assisted Model Building with Energy Refinement (AMBER) [39], Desmond [40], Tinker [40], DL_POLY [41] and others which can be used subjected to the simulation result needed. LAMMPS software by Sandia National Laboratories was applied to simulate the nanoreinforced solder paste environment.…”
Section: Methodology 21 MD Simulation Via Lammpsmentioning
confidence: 99%